Evaluating Southern Ocean Carbon Eddy‐Pump From Biogeochemical‐Argo Floats. Issue 2 (6th February 2018) - Llort, Joan; Langlais, C.; Matear, R.; Moreau, S.; Lenton, A.; Strutton, Peter G.
Abstract: The vertical transport of surface water and carbon into ocean's interior, known as subduction, is one of the main mechanisms through which the ocean influences Earth's climate. New instrumental approaches have shown the occurrence of localized and intermittent subduction episodes associated with small‐scale ocean circulation features. These studies also revealed the importance of such events for the export of organic matter, the so‐called eddy‐pump . However, the transient and localized nature of episodic subduction hindered its large‐scale evaluation to date. In this work, we present an approach to detect subduction events at the scale of the Southern Ocean using measurements collected by biogeochemical autonomous floats (BGCArgo). We show how subduction events can be automatically identified as anomalies of spiciness and Apparent Oxygen Utilization (AOU) below the mixed layer. Using this methodology over more than 4, 000 profiles, we detected 40 subduction events unevenly distributed across the Sothern Ocean. Events were more likely found in hot spots of eddy kinetic energy (EKE), downstream major bathymetric features. Moreover, the bio‐optical measurements provided by BGCArgo allowed measuring the amount of Particulate Organic Carbon (POC) being subducted and assessing the contribution of these events to the total downward carbon flux at 100 m (EP100). We estimated that the eddy‐pump represents less than 19% to the EP100 in the Southern Ocean, although we observed particularly strong events able to locally duplicate the EP100. This approach provides a novel perspective on where episodic subduction occurs that will be naturally improved as BGCArgo observations continue to increase. Plain Language Summary: The vertical transport of surface organic carbon into the deep ocean is a fundamental question in oceanography. This transport of carbon supports ocean ecosystems and influences the global climate. Recently, several studies have observed that vertical transport can occur as short‐lived events. These events are the most efficient way to inject surface organic carbon into the ocean, yet they are extremely hard to observe. In this study, we used autonomous floats to capture them. The observations made by these floats during the last 3 years allowed us to map, for the first time, the spatial distribution of vertical transport events throughout the Southern Ocean. Interestingly, we found that these events were concentrated in regions where ocean currents interact with bathymetry. Moreover, our study provides an innovative approach to observe the episodic transport of carbon from autonomous floats. Key Points: We use Argo floats equipped with biogeochemical sensors to detect subduction events in the Southern Ocean We found that events were concentrated in hot spots of high eddy activity, downstream major topographic features Our results suggest that the contribution of this mechanism to the biological carbon pump in the Southern Ocean might be lower than previously proposed